Efficiency of Resources Use in Cattle Milk Production in the Lower Brahmaputra Valley Zone of Assam, India - Ahmed, Rizwan; Singh, Soibam Basanta; Singh, Ram; Hemochandra, Laishram; Singh, Rajkumar Joshmee (Indian Journal of Dairy Science, 2025)
From the perspective of profit-making in dairy farming, it is essential to understand how to make the most of limited resources for milk production. It is essential to know if the resources owned and utilized by the farmers were utilised effectively or not. The study was undertaken to analyze the resource use efficiency in the cattle milk production in the Lower Brahmaputra Valley Zone of Assam. Multi stage random proportionate sampling technique was undertaken from a cluster of villages and a total of 172 dairy farmers were randomly selected from the two districts, namely Kamrup and Barpeta for the study. Data was collected through interview method using a pre tested semi structured interview schedule. To estimate the productivity of resources in milk production, Cobb Douglas Production Function was used. The co-efficient of multiple determinations was 0.825 and 0.796 for the local and crossbred cattle, indicating that the five variables selected for the analysis had explained 82.5 per cent and 79.6 per cent variation in local and crossbred cattle milk production respectively. The results of Cobb-Douglas Production Function revealed that variables like concentrate, green fodder and labour had positive and highly significant influence on milk production of local cattle whereas for crossbred cattle green fodder, concentrate, dry fodder and veterinary charges had significant influence. The result of allocative efficiency of resources in milk production revealed that concentrates, labour and veterinary charges were under-utilized, whereas green fodder and dry fodder were over-utilized.